2021
DOI: 10.1111/scd.12575
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of methotrexate‐induced oral ulcers in rheumatoid arthritis patients

Abstract: Aim: There is a deficiency in the data concerning the clinical forms of methotrexate-induced oral ulcers. This study was conducted to stratify clinical forms of methotrexate-induced oral ulcers in rheumatoid arthritis patients. Methods: This study included rheumatoid arthritis patients receiving methotrexate as monotherapy. All eligible patients were subjected to thorough clinical examination and full history to identify oral events. Drug history, dose, and duration of MTX were recorded.Results: Among 794 rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The oral ulcers as manifestations of EM related to MTX are rare and there is not one case reported in the literature. Despite this condition, a study showed 6.2 % of oral ulcers in patients receiving MTX (Magdy & Ali, 2021), but there is no information as to this resulting in EM. These considerations made this case report relevant to physicians, nurses and dentists to diagnose and treat patients with oral ulcers and EM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral ulcers as manifestations of EM related to MTX are rare and there is not one case reported in the literature. Despite this condition, a study showed 6.2 % of oral ulcers in patients receiving MTX (Magdy & Ali, 2021), but there is no information as to this resulting in EM. These considerations made this case report relevant to physicians, nurses and dentists to diagnose and treat patients with oral ulcers and EM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a higher prevalence of EM in young adult men (20 to 40 years) (Hani et al, 2000;Blanes et al, 2005;Sanchis et al, 2010;Celenano et al, 2015;Kechichian et al, 2018;Magdy & Ali, 2021), however, in the current clinical case and most cases of EM associated with the use of MTX used in Table I (9/11), were women over the age of 50 (Omoregie et al, 2011;Troeltzsch et al, 2013;Jimbu & Demitsu, 2014;Lee et al, 2015;Katsoulas et al, 2016;Nam, 2018). Certainly, cases of EM associated with the use of MTX in women and older age groups may be related to a higher incidence of arthritis and psoriasis in adult women, in addition to the fact that the elderly population has more comorbidities and uses a greater amount of medication.…”
Section: Discussionmentioning
confidence: 99%